Models and solution algorithms for container terminal operations - Shi, Yanfeng (2019)
Containerization technique greatly improves the efficiency of international cargo shipping. Container terminals, as the service gateways of hinterland transport and maritime transport, plays a crucial role in the process of cargo transport. As most of the problem in container shipping are formulated as integer programming or mixed integer programming which are hard to solve, we propose a benders decomposition method for generic integer programming problems in this thesis. In containerized ocean shipping, container stowage plan greatly affect the operation efficiency in container terminal. In this thesis, we modelled the container stowage slot planning problem from a multi-port view. A multiport view of slot planning is essential in reducing the negative interactive effect of stowing containers in the subsequent port of call. Another challenging problem in container terminal is quay crane scheduling problem. To improve the efficiency of QCs, one strategy is adopting double cycling technique, which enables quay cranes to carry out unloading after loading activity or loading after unloading activity in each cycle. This indeed converts the idle moves of quay cranes with only single cycling into productive moves. In the thesis, we present a model formulation for the quay crane scheduling problem considering double cycling techniques. Two efficient solution methods are proposed to solve the problem fastly.